Statement and Action Agenda from the Girls in Emergencies Collaborative - Omar Robles; Judith Bruce; Holly G. Atkinson; Dale Buscher; Karen Scriven; Kristin Kim Bart; Shelby French (Ubiquity Press, 2015)
Organizations that have signed on to the Girls in Emergencies Collaborative Statement and Action Agenda as of September 2015 include the International Rescue Committee; Mercy Corps; Human Rights Program, Arnold Institute of Global Health at Mount Sinai; Plan USA; the Population Council; and the Women's Refugee Commission. This statement outlines a collective effort to confront the failure to address the needs of adolescent girls in emergencies who are displaced within and across borders around the world.